2019
DOI: 10.18502/keg.v1i2.4441
|View full text |Cite
|
Sign up to set email alerts
|

Microfibrillation of Coir Using High Speed Blender to Improvement of Tensile Behavior of Coir Reinforced Epoxy Composites

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…However, Mulinari et al, [100] treated coconut fibre with a 1% (w/v) of alkaline solution and revealed increased surface roughness through SEM images as a result of the effective removal of wax, pectin, lignin, hemicellulose, and debris from the surface. Marwardi et al, [101] treated coconut coir fibre in a 5% NaOH solution at a temperature and time of 80°C and 600 seconds, respectively, revealing changes in the morphology of the fibre with a reduction in fibre diameter up to 40%, which causes improvement in the matrix-fibre relationship, increased flexural strengths due to improving the aspect ratio of the fibre in addition to a good interface between the composite constituents [102]. However, Oladele et al, [103] reported that optimum mechanical properties were observed in fibre treated with 20% NaOH, and it was concluded that alkaline treatment greatly improves the hydrophobicity of coir fibres.…”
Section: The Hydrophilic Behaviour and Surface Modifications Of Fibre...mentioning
confidence: 99%
“…However, Mulinari et al, [100] treated coconut fibre with a 1% (w/v) of alkaline solution and revealed increased surface roughness through SEM images as a result of the effective removal of wax, pectin, lignin, hemicellulose, and debris from the surface. Marwardi et al, [101] treated coconut coir fibre in a 5% NaOH solution at a temperature and time of 80°C and 600 seconds, respectively, revealing changes in the morphology of the fibre with a reduction in fibre diameter up to 40%, which causes improvement in the matrix-fibre relationship, increased flexural strengths due to improving the aspect ratio of the fibre in addition to a good interface between the composite constituents [102]. However, Oladele et al, [103] reported that optimum mechanical properties were observed in fibre treated with 20% NaOH, and it was concluded that alkaline treatment greatly improves the hydrophobicity of coir fibres.…”
Section: The Hydrophilic Behaviour and Surface Modifications Of Fibre...mentioning
confidence: 99%
“…Setelah dilakukan proses pendinginan, serat dilakukan proses fibrilisasi dengan menggunakan blender putaran tinggi dengan kecepatan 20.000 -30.000 rpm selama 5 menit. Proses ini bertujuan untuk mereduksi diameter serat dan merujuk pada penelitian sebelumnya yang menghasilkan sifat mekanis meningkat setelah serat dilakukan proses fibrilisasi [20].…”
Section: Prosesunclassified